Analyzing the learners’ needs in mobile language application in Arabic for mutawwif (umrah tour guide)/51242 - Sahrir, Muhammad Sabri; Yahaya, Mohd Firdaus; Zubir, Muhamad Azhar; Ismail, Taufik (Global Business and Social Entrepreneurship Resources, 231A, Jalan Bandar 13, Taman Melawati, 53300 Kuala Lumpur, 2017)
The teaching and learning of the Arabic language has been using traditional methods and textbooks for a very long time. The language has been used and taught for various reasons including communication purpose. However, in this era of Information and Communication Technology (ICT), the needs to produce the interactive and technology-based learning and teaching tools have been the area of research by various fields of knowledge. Hence, the huge use of mobile gadgets as Tablet PC, smartphones, I-Pads and so on has the learners to adapt with the mobile revolution in their learning preference of various educational application such as many Apps that are available in Google Store. This project will be focusing on the design and development of a mobile language guide application in Arabic language for Mutawwif (Umrah Tour Guide) VIA smart phones especially in Android supported platforms. Once completed, the project is expected to produce a mobile App of teaching and learning Arabic among Mutawwif (Umrah Tour Guide) via interactive mobile App prototype, which could enhance the learners’ self-motivation and language learning for traveller’s purpose. It will be helping the Mutawwif to communicate in Arabic more effectively and efficiently. The App also has the potential market to be commercialized and expanded to others umrah and Hajj travel and tours companies in Malaysia and all over the world.